PENGARUH PERSEPSI TERHADAP ‘SPOTIFY WRAPPED’ DAN PERSEPSI KEUNTUNGAN PREMIUM TERHADAP MINAT BERLANGGANAN SPOTIFY PREMIUM - Ramadhinda, Azzahra; Manalu, S. Rouli; Pradekso, Tandiyo (Interaksi Online, 2024)
Various efforts have been made by Spotify to attract people to subscribe to Spotify Premium, such as offering different types of premium service packages with various benefits and informational services like Spotify Wrapped. However, the presence of Spotify Wrapped and the benefits of Spotify Premium have led to both positive and negative perceptions among the public. This research will analyze whether the perceptions of Spotify Wrapped and the premium benefits influence the interest in subscribing to Spotify Premium. The theory used in this research is the Technology Acceptance Model (TAM). The sampling technique used in this research is non probability sampling, with a sample of 100 respondents residing in DKI Jakarta. This research conducts hypothesis testing using multiple linear regression equations. The results show that the variables of perception towards 'Spotify Wrapped' and the premium benefits variables simultaneously influence the interest in subscribing to Spotify Premium with a significance value of 0.002 < 0.05. Additionally, the value of the coefficient of determination (R Square) shows a value of 0.116, which means that the perception values towards 'Spotify Wrapped' and the perception of premium benefits towards the interest in subscribing to Spotify Premium are 11.6%. The hypotheses proposed in this study are accepted, and the research findings are in line with the theory used in this study, where the two independent variables in this research can provide benefits to the public and increase the interest in subscribing.